"LET'S CLEAN UP" a Game for Childrens Hygiene Learning - Nurvianto Nugraha Putra; Hendra Prasetya; Dwiyoga Widiantoro (SISFORMA, 2016)
Health is an absolute need for all human beings. When healthy, the human body can perform all activities smoothly. So we should always keep good hygiene themselves and the environment in which we live. Education about hygiene should be taught from an early age. So that children can understand the importance of maintaining hygiene for health. In addition to media learning through formal education, alternative media can be used as a medium of learning for children. Then designed game "Let's Clean Up" the theme of hygiene to children by using the application Construct 2. The objective of this study was to design a medium of learning about hygiene through games